(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rahmawaty, Ginting Y, Batubara R, Rauf A. 2024. The potential for the cultivation of Styrax benzoin based on land suitability evaluation in Pakpak Bharat District, Indonesia. Biodiversitas 25: 1071-1080. Styrax benzoin (kemenyan), a latex-producing plant native to North Sumatra Province, requires development and sustainable cultivation. Currently, it is increasingly common to cultivate S. benzoin in conjunction with other crops, including gambir (Uncaria gambir). This research focused on assessing the suitability of land in Pakpak Bharat Regency for cultivating S. benzoin on land previously used for U. gambir cultivation. In this research, a survey methodology was employed, involving purposive soil sample collection from areas previously used for U. gambir cultivation. These specific locations were Aornakan I Village in Pergetteng Getteng Sengkut Sub-district and Kuta Tinggi Village in Salak Sub-district, both within Pakpak Bharat Regency, North Sumatra Province. The suitability assessment of cultivating S. benzoin on land previously used for U. gambir cultivation employed the matching method. The results revealed that the actual land suitability for S. benzoin was classified as moderately suitable (S2). Land Unit 1 is constrained by factors such as water availability (wa), root media (rc), and erosion hazards (eh), while Land Units 2, 3, and 4 with limitations primarily related to water availability (wa) and root media (rc). The findings also suggest that the potential land suitability class for S. benzoin remains at S2 for growth in areas where U. gambir was cultivated, with notable restrictions related to water availability and root media across all land units.